Na stičišču literature in geografije - Urbanc, Mimi (Slavistična revija, 2012)
Literary works as discursive articulation of the experience of residing in a space are becoming a legitimate subject of geographic inquiry. Postmodern geography also has adopted for its purposes some concepts from literary studies, such as intertextuality and landscape as text or geographic imagination. A qualitative analysis of selected examples of literary texts that thematize the space of Slovene Istria shows how topophilia, the Self/other identity distinction, and feelings of place and placelessness take shape in them. These are contemporary concepts of humanistic geography, which build on the predominantly objectivist, natural and social science tradition by taking into account individual and group apprehension, imagination, and formation of space. Literary works enable geography to analyze our relation to our living environs and the meanings that we attribute to the space or identify ourselves with. Our relations to space are also a fundamental condition for forming identities and societal responsibility.
Keywords: literarna geografija; literary geography; Slovene Istria; Slovene literature; Slovenian Istria; slovenska Istra; slovenska književnost